2014
DOI: 10.3390/soc4020330
|View full text |Cite
|
Sign up to set email alerts
|

“Maternal Devices”, Social Media and the Self-Management of Pregnancy, Mothering and Child Health

Abstract: Abstract:In recent years the smartphone has revolutionised lay people's management of health and illness, particularly in regards to pregnancy and parenting. This article analyses smartphone applications, or apps, and social media platforms as mediating technologies which act as performative devices. These devices encourage particular enactments of subjectivity and technologies of the self which combine the expert patient ideal with ideologies of mothering. Some apps and social media can be disciplinary and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 36 publications
2
104
0
4
Order By: Relevance
“…Whether the data related to height and weight or sleeping and feeding, the respondents appreciated the more interactive apps for their ability to store and manage data and therefore 'personalise' the outputs of the app. Other researchers have also identified the desire of women to use apps that provided personalised information tailored to their needs 17,20,30 . The emphasis on visual aids could be part of a need for 'titbits' of information on the part of busy mothers who do not have time to read pamphlets or books to pick out the pieces of information relevant to their needs, but might also be attractive to women who have literacy difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the data related to height and weight or sleeping and feeding, the respondents appreciated the more interactive apps for their ability to store and manage data and therefore 'personalise' the outputs of the app. Other researchers have also identified the desire of women to use apps that provided personalised information tailored to their needs 17,20,30 . The emphasis on visual aids could be part of a need for 'titbits' of information on the part of busy mothers who do not have time to read pamphlets or books to pick out the pieces of information relevant to their needs, but might also be attractive to women who have literacy difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…This research found that 40% of the women reported using at least one pregnancy-related app. A small Sydney-based study involved interviews with perinatal women about a range of experiences in pregnancy and early parenting 20 . Some of the participants spontaneously raised the issue of using apps and remarked that they appreciated the convenience offered by apps for accessing information about the development of their pregnancy.…”
Section: Another Project Involved Conducting Qualitative Interviews Wmentioning
confidence: 99%
“…Indeed, Johnson (2014) argues further that the visible use of apps, devices, and other tools which can be shared via social media can be situated as part of the "responsibilisation" of motherhood, in which access to greater information and data about pregnancy and the unborn simultaneously increases the expectation of specific ways of acting and self-policing the process of pregnancy and birth. This process is reinforced by the expectation of sharing information about prenatal experiences.…”
Section: Pregnancy To Infancymentioning
confidence: 99%
“…The discussion here presented contributes to previous work in this area in several ways: by focusing on the experiences of Australian women (a group that has received little attention thus far); by addressing the full panoply of digital media that are now available to women for both pregnancy and parenting rather than focusing on one media type alone, as most other studies have done; and by considering the complexities of the intersections between information, emotional support, intimacy, personal data generation, sharing and privacy as they are conducted and experienced on the digital media used by women during these life stages. The handful of studies published thus far on the Australian context have found that women are actively using apps and social media for pregnancy and parenting [18,[27][28][29][30]. However, little research has yet investigated the details of how Australian women take up these media in relation to each other, and across their experiences of pregnancy and into the early parenting period.…”
Section: Introductionmentioning
confidence: 99%